2021
DOI: 10.1016/j.jbc.2021.100531
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor inhibits EMT via regulation of the epithelial mitochondrial function in intestinal fibrosis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 60 publications
(75 reference statements)
3
36
0
Order By: Relevance
“…Johnson et al have demonstrated that CARD-024, a vitamin D analogue was able to reduce ECM-associated markers in TGF-β-stimulated or stiffness-induced colonic fibroblasts [ 60 ]. In addition, down-regulation of colon VDR is observed in chronic CD patients and also in mice with chronic DSS-induced colitis and fibrosis [ 61 ]. VDR is also reduced in fibroblasts from CD patients [ 62 ].…”
Section: Beneficial Effects Of Dietary Componentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Johnson et al have demonstrated that CARD-024, a vitamin D analogue was able to reduce ECM-associated markers in TGF-β-stimulated or stiffness-induced colonic fibroblasts [ 60 ]. In addition, down-regulation of colon VDR is observed in chronic CD patients and also in mice with chronic DSS-induced colitis and fibrosis [ 61 ]. VDR is also reduced in fibroblasts from CD patients [ 62 ].…”
Section: Beneficial Effects Of Dietary Componentsmentioning
confidence: 99%
“…Mitochondrial dysfunction has been described in patients with IBD and genetic deletion of prohibitin 1, a key protein of the inner mitochondrial membrane decreased in IBD, which can provoke ileitis in mice [ 63 ]. VDR is also involved in mitochondrial dysfunction [ 61 ] and its specific role in intestinal fibrosis has been recently demonstrated [ 61 ]. The authors of this elegant study first demonstrated that VDR expression was lower in intestinal stenotic areas in CD patients [ 61 ].…”
Section: Beneficial Effects Of Dietary Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that the activation of the Wnt/β-catenin signaling pathway is highly involved in the process of various organ fibrosis [3] such as renal [4], liver [5], peritoneal [6], and dermal fibrosis [7]. Studies also found that the upregulation of the vitamin D receptor (VDR) might contribute to the alleviation of organ fibrosis [8]. Moreover, VDR gene can regulate the expression of many genes, and the analysis of Targetscan database by Cong [9] suggested that Wnt gene and βcatenin gene may be potential targets of VDR protein.…”
Section: Introductionmentioning
confidence: 99%